Slow movies : countering the cinema of action - Jaffe, Ira, 1943- (Wallflower Press, 2014)
?In all film there is the desire to capture the motion of life, to refuse immobility," Agnes Varda has noted. But to capture the reality of human experience, cinema must fasten on stillness and inaction as much as motion. Slow Movies investigates movies by acclaimed international directors who in the past three decades have challenged mainstream cinema's reliance on motion and action. More than other realist art cinema, slow movies by Lisandro Alonso, Nuri Bilge Ceylan, Pedro Costa, Jia Zhang-ke, Abbas Kiarostami, Cristian Mungiu, Alexander Sokurov, Bela Tarr, Gus Van Sant and others radi